Comparative Analysis of Community Energy Projects: Policy Lessons for Kenya from the United Kingdom - Kitony, Sharon; Onyango, Vincent; Duot, John Deng; Ologhadien, Nelson Goodnews; Pouhe, Stephanie Ngo (European Scientific Journal, ESJ, 2024)
Assuming a scope for policy learning across jurisdictions, this paper compared policies relevant to community energy projects (CEPs) in a developed country where they have been adopted (i.e. the UK), against policies in an emerging country where CEPs are scarce (i.e. Kenya). Through comparative analysis, successes and failures in the policies’ landscapes were examined, with the aim of distilling lessons that could enhance CEPs adoption in Kenya. Both countries have some similar core functional mechanisms in their policies, e.g. Feed-in-Tariffs, energy auctions, and grid access. These are demand-side in nature and create a market for CEPs while derisking investments to local communities. However, key differences exist, reflecting the levels of maturity in the energy mix and policy-making in either country. The UK has more demand-side and ‘implementation oriented’ policies, compared to Kenya. For Kenya, key lessons include incentives prioritising appropriate grant programs, Feed-in-Tariffs targeting CEPs, adopting Smart Export Guarantee, implementing grid connection agreements, and fostering centres for data and knowledge exchange. However, these require a laser-focus to make them bespoke to the Kenyan context. Our recommendations envisaged a carefully calibrated confluence of pull-push policy factors, involving: a CEPs-friendly policy landscape, CEPs targets under a long-term strategy, natural abundance of different RE sources, and, Kenya’s appetite for using different policy solutions for different needs. Two key areas for relevant research are worth mentioning: exploring where the equilibrium for cost-effective energy mix integrating CEPs lies, in Kenya’s future, and; empirically exploring systems-wide analyses to reveal the inter-dependencies and inter-relations of the various contextual and policy factors, aimed at CEPs as an outcome.